Rate of exciton scattering and exciton absorption in crystals with LO-phonon dispersion - Grigorchuk, N.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Using the Ridley–Babiker relation for the LO-phonon energy, an exact formula for the exciton scattering rate in the one-phonon approximation is obtained. The effect of LO-phonon dispersion on the frequency and temperature dependence of the exciton attenuation is studied theoretically for the models of polar crystals with large and small exciton radii. It is shown that the role of LO-phonon dispersion is essentially different in processes with phonon absorption and phonon emission. For some fixed frequency interval, it is established that the effect of dispersion on exciton scattering is changed with temperature. The TlBr and ZnS crystals were chosen as the models for illustrations.